PENANGANAN PREMANISME OLEH TIM PEMBURU PREMAN DI WILAYAH HUKUM POLRES METRO JAKARTA BARAT - M. Ainun Ilham Arifin; Mona Minarosa (Constitutum: Jurnal Ilmiah Hukum, 2023)
The phenomenon of thuggery that occurs in the jurisdiction of the West Jakarta Metro Police which is so disturbing to the public is the responsibility of the National Police as the custodian of security and order. Therefore, the West Jakarta Metro Police has formed a Thug Hunting Team which is expected to be able to carry out efforts to overcome thuggery. Based on this, two problems can be formulated, namely how the Thug Hunting Team's efforts to deal with thuggery in the jurisdiction of the West Jakarta Metro Police and whether the Thug Hunting Team's actions can reduce the crime rate in the jurisdiction of the West Jakarta Metro Police. The research methods used are normative juridical and empirical. The results of the research show that the Thug Hunting Team's efforts in handling thuggery in the jurisdiction of the West Jakarta Metro Police are carrying out routine patrol activities at 20.00-08.00 WIB, namely by combing areas that are considered prone to thuggery. This effort is prioritized through a dialogue strategy with the thugs. Apart from that, the Thug Hunting Team takes legal action based on reports received from the public or uploading viral videos on social media or carrying out actions via social media networks. The actions of the Thug Hunting Team in reducing the crime rate in the jurisdiction of the West Jakarta Metro Police are considered quite successful.